Draft Genome Sequencing of the Pathogenic Fungus Cladosporium phlei ATCC 36193 Identifies Candidates of Novel Polyketide Synthase Genes Involved in Perylenequinone-Group Pigment Production. (February 2019) - Kang, Yu-Na; So, Kum-Kang; Kim, Do-Wan; Kim, Dae-Hyuk; Lee, Tae-Ho
Cladosporium phlei, which causes purple eyespot disease, has been focused on as a source of phleichrome from the perylenequinone group of pigments. Although this agent is important in photodynamic therapy, there are no genome sequences for the species. Here, we sequenced the genome of C. phlei and reported the draft sequence. The total length of the draft genome was approximately 31.8 Mb, and 9571 genes were predicted. Phylogenetic analysis showed that Cladosporium sphaerospermum, Rachicladosporium sp., and Rachicladosporium antarcticum were closely related, and this result corresponded to the taxonomic data. In addition to the draft genome sequence, we report four candidates of new polyketide synthase (PKS) genes, involved in the production of perylenequinone-group pigments.